Defensive Works of Subarctic Snow - Johnson,Philip R (1977)
It has been reported that small arms projectiles are inherently unstable in snow and that snow has an unexpectedly high ability to stop them and other fast-moving projectiles. Field tests showed that the typical subarctic snow of interior Alaska can be used effectively to provide protection from both rifle and machine gun fire. The undisturbed snow had an average density of 0.18 g/cu. cm., but simple processing, such as shoveling, increased the density to around 0.34 g/cu. cm. Further processing increased the density to above o.40 g/cm3 but densities much above that value were difficult to obtain with simple hand equipment. Tests of the M16 rifle and M60 and M2HB machine guns showed that bullet penetration was inversely related to density - the higher the density the lower the bullet penetration. Design values for the three weapons were determined. A number of types of snow trenches and structures were designed and tested. They were found to provide good protection, in part since bullets showed a strong tendency to ricochet from the snow surface when striking it at a low angle. Burlap bags were filled with snow to revet structures and worked very well. Several types of Russian defensive works of snow were tested but proved unsuitable in the light, weak subarctic snow. The times required for troops to build several types of structures using only shovels and scoops were recorded.